PELATIHAN PEMBUATAN PUPUK ORGANIK BOKASHI DARI KOTORAN TERNAK DI LEMBANG PAKALA - Kannapadang, Sepsriyanti; Kannapadang, Dwibin; Oktafianus, Sion (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This community service program activity was carried out in Lembang Pakala, Mengkendek District, Tana Toraja Regency. Where most of the people are buffalo and cattle breeders. The business of buffalo and cattle breeders produces waste in the form of good livestock manure. Feces and urine as well as remaining animal feed. One effort to reduce environmental pollution is to use livestock waste as fertilizer. One type of organic fertilizer that is currently being developed is bokashi. Bokashi in Japanese means “gradual change”. The method used in this activity is counseling and training for cattle and buffalo breeders. In connection with this training activity, the program orientation is management of livestock waste processing with the aim of reducing environmental pollution, utilizing waste into quality products, as well as efforts to improve community welfare